THE WEST AND NON-WEST: A NEW APPROACH TO THE OLD DICHOTOMY - D. A. Kuznetsov (MGIMO University Press, 2016)
Book review: Martynov, B.F. The West and Non-West: the Past, the Present... the Future? Moscow: Institute of Latin American Studies of the Russian Academy of Sciences, 2015. 172 p.